Financial Sustainability Analysis and Monetization of Halal Lifestyle Blog and Podcast Content in the Global Market: ANALISIS KEBERLANJUTAN KEUANGAN DAN MONETISASI KONTEN BLOG SERTA PODCAST GAYA HIDUP HALAL DI PASAR GLOBAL - Hardiyanti, Sri; Adinugraha, Hendri Hermawan (Ekonomipedia: Jurnal Ekonomi Manajemen dan Bisnis, 2025)
Abstract. The global halal industry is growing not only in the food and beverage sector, but also in digital media through blogs and podcasts on the theme of halal lifestyles. These platforms serve as a means of education and da'wah while also opening up monetization opportunities in the digital creative economy. This study analyzes monetization strategies and their relationship to financial sustainability through a qualitative literature review of journals, industry reports, and international publications. The results of the study show that financial sustainability can be achieved through diversification of advertising models, sponsorship, affiliation, subscription, merchandise, and crowdfunding tailored to the audience. Integration with halal cuisine, fashion, tourism, and sharia financial support further strengthens sustainability. Abstrak. Industri halal global berkembang tidak hanya pada sektor makanan dan minuman, tetapi juga ke media digital melalui blog dan podcast bertema gaya hidup halal. Platform ini berfungsi sebagai sarana edukasi dan dakwah sekaligus membuka peluang monetisasi dalam ekonomi kreatif digital. Penelitian ini menganalisis strategi monetisasi dan kaitannya dengan keberlanjutan finansial melalui studi pustaka kualitatif atas jurnal, laporan industri, dan publikasi internasional. Hasil penelitian menunjukkan ketahanan finansial dapat dicapai melalui diversifikasi model iklan, sponsorship, afiliasi, subscription, merchandise, dan crowdfunding yang disesuaikan dengan audiens. Integrasi dengan kuliner, fesyen, pariwisata halal, serta dukungan keuangan syariah semakin memperkuat keberlanjutan.